Nodal Demand Control Genetic Algorithm for Water Supply Systems - Bylka, Jedrzej; Bałut, Alicja; Brodziak, Rafał; Zakrzewski, Przemysław (Instal, 2022)
The management of water distribution networks is nowadays exposed to various hazards, and their operations need to meet a range of critical conditions, new to the industry, that need to be addressed and solved. This article describes an approach that could be applied in case of intermittent deficit of water supply, by controlling the nodal demand in a water supply network. The article provides a mathematical approach to meeting minimum required water demand in case of supply shortages. Based on a simple hydraulic model case study, a genetic algorithm is implemented to find optimal valve settings which provide a minimum supply of water under water deficit conditions. The results highlight limitations and advantages relating to the time taken to perform calculations. Moreover, some practical aspects are pinpointed in the discussion section.